Efficiency of application of physical methods of drying intensification to various tobacco varieties - E. E. Ulyanchenko; E. V. Gnuchikh; N. N. Vinevskaya (Новые технологии)
Intensification of tobacco leaves drying is achieved due to the physical method of cutting the middle vein of the leaf. The method of cutting costae is applied to various varieties of tobacco used in mixtures in the manufacture of smoking products. The aim of the research is to determine the effect of cutting on the quality indicators of raw materials of various varieties of tobacco used in the mixtures when a natural method of drying is used. The dynamics and intensity of drying of different varieties of tobacco with cut costae have been studied in comparison with a whole leaf. It has been found that the dried raw material has a different final equilibrium moisture, which determines its hygroscopic properties. The influence of hygroscopic properties of various varieties on the technological parameters of the raw material has been determined. It has been established that the method of cutting costae in all types of tobacco reduces the drying time by 1.3-2.5 times, does not impair the commodity quality of the raw materials, improves its technological properties, the fiber yield increases to 1.58-6.85%, dust yield does not exceed the regulated values, does not significantly affect changes in the chemical indicator of nicotine level.